Stepwise dual stimuli triggered dual drug release by a single naphthalene based two-photon chromophore to reverse MDR for alkylating agents with dual surveillance in uncaging steps. Issue 87 (16th October 2019) - Roy, Biswajit; Kundu, Moumita; Singh, Amit Kumar; Singha, Tara; Bhattacharya, Sayantan; Datta, Prasanta Kumar; Mandal, Mahitosh; Singh, N. D. Pradeep
Abstract : A single chromophore based dinitrophenylsulphonyl–naphthalene–chlorambucil conjugate drug delivery system is presented for the dual stimuli controlled release of SO2 and chlorambucil. Abstract : In this work, we depleted glutathione (GSH) by releasing SO2 with internal stimulus GSH itself, and also selectively marked the cancer cells followed by release of anticancer drug using another orthogonal stimulus i.e., two-photon (TP) NIR light by a single naphthalene based chromophore (TP absorbance 77 GM and uncaging cross-section 21 GM). We demonstrated the improved therapeutic efficacy of chlorambucil by the stepwise dual stimuli approach and dual surveillance of both the drug uncaging process in real-time using in vitro studies.